2002
DOI: 10.1071/sr01057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cattle treading on interrill erosion from hill pasture: modelling concepts and analysis of rainfall simulator data

Abstract: Damage to pasture as a result of intensive grazing and treading by cattle increases the erosion of sediment and associated nutrients. In this study we present a model for the effect of treading damage on interrill erosion. The model formulation is based on the interrill erosion components of conventional process-based erosion models, with some modifications. The model was developed using data from small rainfall simulator plots (0.5 m2) on hill-country pasture in New Zealand with varying amounts of treading da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 10 publications
0
32
1
Order By: Relevance
“…There have been several earlier studies of runoff generation at Whatawhata (in or near to the Pukemanga catchment). Elliott et al (2002) used small rainfall simulator plots (0Ð5 m 2 ) to study the effects of cattle tramping on runoff and erosion. Cattle tramping was observed to damage pasture (viz., to increase the area of bare soil) and the flow-weighted mean concentration of suspended solids in runoff was strongly correlated with the percentage of bare soil.…”
Section: Methodsmentioning
confidence: 99%
“…There have been several earlier studies of runoff generation at Whatawhata (in or near to the Pukemanga catchment). Elliott et al (2002) used small rainfall simulator plots (0Ð5 m 2 ) to study the effects of cattle tramping on runoff and erosion. Cattle tramping was observed to damage pasture (viz., to increase the area of bare soil) and the flow-weighted mean concentration of suspended solids in runoff was strongly correlated with the percentage of bare soil.…”
Section: Methodsmentioning
confidence: 99%
“…Total P load in runoff from rainfall simulations in the late spring (0.072 6 0.006 kg ha À1 h À1 ) was greater (P , 0.05) than during the other seasons, which did not differ, and averaged 0.024 6 0.006 kg ha À1 h À1 . Elliott et al (2002) reported similar seasonal variability in sediment load in surface runoff from pasture, with peak erosion occurring during the wetter portion of the year.…”
mentioning
confidence: 68%
“…Damage caused by treading (Elliott et al 2002), decreased soil organic matter (Naeth et al 1991b;Betteridge et al 1999), and reduced leaf litter results in a reduction of aboveground water-holding capacity of the soil (Naeth et al 1991a), decreasing infiltration rate and increasing the volume of surface runoff. Management practices that reduce the total volume of surface runoff and encourage infiltration will reduce the potential for sediment and P losses from pastures (Gburek et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of bare soil is a major factor associated with soil erosion (Russell et al 2001;Haan et al 2006). Not surprisingly, concentration of sediment in surface runoff has been linearly related to the amount of bare ground of a given area, as exposed soil is more susceptible to soil detachment by overland flow (Hofman and Ries 1991;Elliott et al 2002;Persyn et al 2004) and erosive energy of raindrops (Young and Wiersma 1973;Morgan 1978;Kinnell 2005). As a result, bare ground in riparian areas of pastures may contribute significant sediment and phosphorus loads to surface waters during heavy rainfall events (Line et al 2000;Byers et al 2005;Butler et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of stubble height alone has been reported to be not suitable to predict sediment infiltration (Pearce et al 1997, Haan et al (2006) reported lower quantities and phosphorus loading of runoff from pastures that were rotationally stocked to a residual height of 10 cm than in pastures continuously stocked to a residual height of 5 cm in cool-season grass pastures. By maintaining adequate vegetation cover and height, plant vigor may be preserved (Frazier et al 1998;Clary and Leininger 2000) and reduce NPS pollution from riparian areas of pastures (Warren et al 1986;Elliott et al 2002;Reed and Carpenter 2002). In the current study, forage sward heights within riparian areas of pastures quadratically increased as the proportion of reed canarygrass increased y~4:06z0:40x{0:0027x 2 r 2~0 :42…”
Section: Forage Sward Heightmentioning
confidence: 99%